Performance of Fiber Reinforced Mortar coating for irregular stone masonry: Experimental and analytical investigations. (2nd August 2021) - Angiolilli, Michele; Gregori, Amedeo; Cattari, Serena
Highlights: Mechanical characterization of stone masonry panels extracted from an existing building. Investigation of the property evolution of masonry during cyclic compression tests. A new analytical formulation is validated through 60 literature tests. Increasing thickness and tensile strength of the FRM mortar positively affect the masonry shear strength. FRM performance is lower for URM characterized by higher thickness and/or shear strength. Abstract: Nowadays, the application of Fiber Reinforced Mortar (FRM) is widely used for the consolidation and rehabilitation of masonry structures because represents an effective solution in terms of reversibility and applicability. The paper illustrates the results of cyclic diagonal compression tests performed in situ on stone masonry specimens isolated from the walls of a historic building of L'Aquila (Italy). The tested stone masonry is representative of existing structures of the territories of the central Apennines in Italy. Only two of four panels were strengthened by FRM to provide also the reference value of the unreinforced masonry. The FRM comprised a glass-fiber grid embedded in a natural hydraulic lime (NHL)-based mortar applied as a coating to the masonry surfaces as well as carbon shear connectors. The tests were analyzed to derive the shear strength and the shear modulus of the masonry, as well as their evolution during the tests. Moreover, these tests were compared and integrated with a consistent number of experimental data collected in the current literature aiming to validate a new analytical equation for the estimation of the shear strength of the reinforced masonry, merely based on the properties of the unreinforced masonry and the FRM mortar.